Hyperresistinemia is associated with postmenopausal breast cancer. - Dalamaga, Maria; Karmaniolas, Konstantinos; Papadavid, Evangelia; Pelekanos, Nicolaos; Sotiropoulos, George; Lekka, Antigoni (Menopause, 2013)
OBJECTIVE: The constellation of obesity, insulin resistance, and serum adipocytokine levels is associated with the risk and prognosis of postmenopausal breast cancer (PBC). Altered secretion of resistin may underlie the association between overweight/obesity and PBC. We thus explored the association of serum resistin with PBC, taking into account established risk factors, including adipokines and anthropometric, metabolic, and inflammatory markers. METHODS: In a case-control study, we studied 102 postmenopausal women with pathologically confirmed, incident invasive breast cancer and 102 control participants matched on age and time of diagnosis between 2003 and 2010 at the Veterans' Administration General Hospital of Athens (NIMTS Hospital). Serum resistin, adiponectin, leptin, metabolic (homeostasis model assessment score of insulin resistance) and inflammatory (tumor necrosis factor-α, interleukin-6, and high-sensitivity C-reactive protein) parameters, and tumor markers (carcinoembryonic antigen and CA 15-3) were determined. RESULTS: The mean serum resistin level was significantly higher in case participants than in control participants (P < 0.001) in both univariate and multivariable analyses, adjusting for age, date of diagnosis, education, family history of cancer, use of exogenous hormones, alcohol consumption, smoking status, physical activity, reproductive markers, metabolic markers, anthropometric (body mass index and weight circumference) markers, inflammatory markers, and adipokines (odds ratio, 1.17; 95% CI, 1.03-1.34; P = 0.02). In case participants, resistin level correlated significantly with tumor markers and inflammatory parameters, but not with metabolic and anthropometric variables. CONCLUSIONS: Further prospective, longitudinal, and mechanistic studies are needed to determine whether hyperresistinemia is involved in the development of PBC or reflects changes during PBC progression and therefore could be used as a biomarker for PBC. Targeting resistin inhibition could be an effective therapeutic strategy in breast cancer by down-regulating the inflammatory microenvironment in breast tissue.
Keywords: Adipokines; Aged; Aged, 80 and over; Biomarkers; Biomarkers, Tumor; Body Mass Index; Breast Neoplasms; C-Reactive Protein; Case-Control Studies; Female; Humans; Inflammation; Insulin Resistance; Interleukin-6; Leptin; Middle Aged; Obesity; POSTMENOPAUSE; Prognosis; Resistin; Risk Factors; Tumor Necrosis Factor-alpha